The Smartphone Paradox Our Ruinous Dependency in the Device Age - Reid, Alan J. (Springer International Publishing, 2018)
The Smartphone Paradox is a critical examination of our everyday mobile technologies and the effects that they have on our thoughts and behaviors. Alan J. Reid presents a comprehensive view of smartphones: the research behind the uses and gratifications of smartphones, the obstacles they present, the opportunities they afford, and how everyone can achieve a healthy, technological balance. It includes interviews with smartphone users from a variety of backgrounds, and translates scholarly research into a conversational tone, making it easy to understand a synthesis of key findings and conclusions from a heavily-researched domain. All in all, through the lens of smartphone dependency, the book makes the argument for digital mindfulness in a device age that threatens our privacy, sociability, attention, and cognitive abilities.